A potential protein-based vaccine for influenza H5N1 from the recombinant HA1 domain of avian influenza A/H5N1 expressed in Pichia pastoris. (December 2014) - Nguyen, Thi Quy; Van, Thi Thu Hao; Lin, Yu-Chen; Van, Thi Nhu Ngoc; Bui, Khanh Chi; Le, Quynh Giang; Do, Thi Huyen; Le, Thi Thu Hong; Vo, Viet Cuong; Truong, Van Dung; Smooker, Peter M; Coloe, Peter J; et al.
ABSTRACT : The HA1 genes from influenza A strains A/Puerto Rico/8/1934 H1N1 (A/PR/8/34) and A/Hatay/2004 H5N1 were each cloned in Pichia pastoris vectors in the correct reading frame with the yeast α-factor secretion signal and the C-terminus His-tag, resulting in simple, fast purification of expressed H1HA1 and H5HA1 protein from the culture medium. Mice vaccinated with the purified proteins showed robust T cell, anti-HA1 IgG responses and developed a high antibody response for hemagglutination inhibition (HI) at titer 7.6 log2 . Chickens vaccinated with a dose of 200 µg of H5HA1 mixed with either Montanide or Freund's adjuvants gave HI values of up to 7 log2 at the third week comparable with a licensed inactivated H5N1 vaccine.